2008
DOI: 10.5511/plantbiotechnology.25.205
|View full text |Cite
|
Sign up to set email alerts
|

Agrobacterium-mediated genetic transformation of radish (Raphanus sativus L.)

Abstract: Radish (Raphanus sativus L.) belongs to the family Brassicaceae, and is an important plant that is cultivated throughout Asia. Korean varieties are rich in vitamins B and C and have important medicinal properties. However, many of these varieties are susceptible to various pathogens and conventional breeding is not successful in introducing resistance genes into the varieties because of limited availability of germplasm. Alternatively, it is required to establish a genetic transformation system of this species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…The use of adventitious shoot growth on hypocotyl explants for Agrobacteriummediated radish genetic transformation was investigated using transgenic radish (Raphanus sativa L., cv. Jin Ju Dae Pyong) grown on Murashige and Skoog medium (Cho et al 2008). Besides, northern blot results revealed the GUS gene transcript was detected in few regenerated plants hence, confirming genetic transformation (Cho et al 2008).…”
Section: Genetic Engineeringmentioning
confidence: 68%
See 1 more Smart Citation
“…The use of adventitious shoot growth on hypocotyl explants for Agrobacteriummediated radish genetic transformation was investigated using transgenic radish (Raphanus sativa L., cv. Jin Ju Dae Pyong) grown on Murashige and Skoog medium (Cho et al 2008). Besides, northern blot results revealed the GUS gene transcript was detected in few regenerated plants hence, confirming genetic transformation (Cho et al 2008).…”
Section: Genetic Engineeringmentioning
confidence: 68%
“…Jin Ju Dae Pyong) grown on Murashige and Skoog medium (Cho et al 2008). Besides, northern blot results revealed the GUS gene transcript was detected in few regenerated plants hence, confirming genetic transformation (Cho et al 2008).…”
Section: Genetic Engineeringmentioning
confidence: 68%
“…of transgenic shoots per hypocotyl explants) of GV3101 was higher than that of the EHA101, and the mean value (GV3101 : 13.3% and EHA101 : 6.2%) also supported the difference. Thus, we could improve the transformation efficiency from 0.26% that was previously described in the publication (Cho et al 2008) to 13.3% using the "Pirabikku" hypocotyl as the explant source. Four transgenic shoots transformed by Agrobacterium strain GV3101 were transferred to shoot elongation medium (B5 medium containing 1 mg l −1 gibberellic acid, 10 mg l −1 hygromycin, 200 mg l −1 carbenicillin, 10 g l −1 sucrose, and 4 g l −1 gellan gum with pH 5.8), and these plants were further grown in a root induction medium (B5 medium containing 2 mg l −1 indole-3-butyric acid, 10 mg l −1 hygromycin, 200 mg l −1 carbenicillin, 10 g l −1 sucrose, and 4 g l −1 gellan gum with pH 5.8).…”
mentioning
confidence: 87%
“…Although these studies have accelerated the investigation of the correlation between the genes and traits, molecular breeding based on the revealed molecular function of these genes has not been developed because a genetic transformation system with high efficiency and reproducibility has not been constructed in Raphanus. In some previous publications on Raphanus transformation, many different methods such as the floral dip (Curtis and Nam 2001), ultrasonic and vacuum infiltration (Park et al 2005), and Agrobacterium-mediated genetic transformation using the hypocotyl explants (Cho et al 2008) have been reported. However, in these methods, the transformation efficiency is insufficient because the number of transgenic plants produced in one experiment is relatively small, which makes the molecular breeding of radish with practical traits unrealistic.…”
mentioning
confidence: 99%
See 1 more Smart Citation